2020
DOI: 10.7554/elife.60462
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric neurogenic commitment of retinal progenitors involves Notch through the endocytic pathway

Abstract: During brain development, progenitor cells need to balance proliferation and differentiation in order to generate different neurons in the correct numbers and proportions. Currently, the patterns of multipotent progenitor divisions that lead to neurogenic entry and the factors that regulate them are not fully understood. We here use the zebrafish retina to address this gap, exploiting its suitability for quantitative live-imaging. We show that early neurogenic progenitors arise from asymmetric divisions. Notch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 85 publications
(138 reference statements)
0
26
1
Order By: Relevance
“…This RPC divides to form an RGC and a ThrbCRM1-like RPC on division. The formation of these cells could be the first change elicited by Notch inhibition which would suggest that RGCs should also increase and may correspond to the Ath5+ RPCs followed in Nerli et al, 2020. We do observe a number of cells in the RGC layer, however, we have not detected an increase in RGCs using early RGC markers such as Islet1 and Brn3.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This RPC divides to form an RGC and a ThrbCRM1-like RPC on division. The formation of these cells could be the first change elicited by Notch inhibition which would suggest that RGCs should also increase and may correspond to the Ath5+ RPCs followed in Nerli et al, 2020. We do observe a number of cells in the RGC layer, however, we have not detected an increase in RGCs using early RGC markers such as Islet1 and Brn3.…”
Section: Discussioncontrasting
confidence: 52%
“…Instead of a multipotent RPC dividing asymmetrically to form another multipotent RPC and a ThrbCRM1 RPC, does Notch inhibition cause symmetrical divisions to form two ThrbCRM1 RPCs? A recent study in the zebrafish retina showed that pharmacological inhibition of Notch signaling led RPCs to transition from an asymmetric mode of division to a symmetric one in which two neurogenic RPCs were produced (Nerli et al, 2020). Our current findings align well with those of this study, with active Notch signaling functioning specifically to maintain multipotent RPCs and inhibit neurogenic (what we refer to as restricted) RPC states.…”
Section: Discussionmentioning
confidence: 99%
“…These observations and additional data on nuclear position and Notch signaling (Del Bene et al, 2008 ) suggest that both cell shape via apical junction remodeling and nuclear position via interphase oscillations impact signaling instructive for cell-fate decisions of RPCs ( Figure 1A ). The cellular mechanisms mediating the relationship between nuclear position, cell shape, and polarized signaling remain elusive, although, endocytosis may play a role (Nerli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The subcellular localization of endosomes can elicit polarized responses to form or modify morphogen gradients, whereas sorting of receptor–ligand complexes to distinct endosomal compartments can either prolong or quench signaling within cells (Lamaze and Prior, 2018 ). Specifically, in the retina, endocytosis was shown to modulate asymmetries in cellular signaling, including Notch signaling pathway activation, to control neurogenic decisions (Nerli et al, 2020 ). Based on these studies, we hypothesize that apical junction remodeling alters signaling in RPCs and biases neurogenic potential in a nuclear position-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous studies where authors monitored closely the activation of the Ath5 promoter in this zebrafish line, reporting the existence of ath5:GFP progenitors that later become photoreceptors, amacrines, or horizontal cells ( Poggi et al, 2005 ). In addition, recent studies show that neurogenic progenitors that arise from asymmetric divisions are Ath5 positive, suggesting that these are reminiscent of the intermediate progenitors found in the mammalian neocortex( Nerli et al, 2020 ). In our analysis, we observe that the percentage of these intermediate progenitor cells is high at initial time points, and then decreases, suggesting that, in average, the percentage of asymmetric divisions is higher at early stages than a later stages of the first wave of differentiation of the developing zebrafish retina.…”
Section: Resultsmentioning
confidence: 99%